Economic Decoupling and Solid Waste Generation in Mexican tourist Municipalities - Flores-Xolocotzi, Ramiro; Ceballos Pérez, Sergio Gabriel (Sociedad y Economía, 2023)
An econometric study on probable economic decoupling was conducted to test an environmental Kuznets curve hypothesis for municipal solid waste (MSW) in 186 municipalities of tourist importance in Mexico for the years 2010 and 2015 using panel data. For this purpose, random effects, fixed effects, and fixed effects models with robust cluster standard errors were estimated, having as independent variables an indicator of municipal income per capita, population density, population, and average schooling. The results significantly support that there is no statistical evidence of decoupling between MSW generation and income and therefore there is no evidence of a probable Kuznets curve for the municipalities studied. However, future research is required that includes more tourist municipalities, a longer time horizon, and spatial relationships between municipalities, in addition to recycling variables.